The Influence Of Current Ratio, Debt To Equity Ratio, Return On Assets, And Total Asset Turnover On Stock Prices - Nurrohmah, Fika; Syah, Muhammad Jusman (Sean Institute, 2025)
This research aims to examine the influence of the Current Ratio, Debt to Equity Ratio, Return on Assets, and Total Asset Turnover on stock prices in coal mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The population in this study consists of 83 coal mining companies listed on the IDX during the 2019–2023 period. A sample of 14 companies was selected from this population using the purposive sampling method. The research data was then processed and analyzed using Multiple Linear Regression with the assistance of SPSS version 25. The results of the hypothesis testing indicate that the Current Ratio, Debt to Equity Ratio, and Total Asset Turnover have no significant effect on stock prices. However, Return on Assets has a positive and significant effect on stock prices.